2011
DOI: 10.1590/s1517-83822011000300046
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of outbreak hepatitis a isolates in five Tunisian childcare centers

Abstract: In the present study, epidemiological survey and molecular characterization of hepatitis A virus during an outbreak in five Tunisian childcare centers in El-Mahres during October and November 2006 were carried out. Five well-water and five drinking water samples were included in the present study. Serological investigation and molecular characterization were carried out. All patients were IgM seropositive and the viral genome was detected in all clinical and well-water samples whereas it was not detected in dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The most prevalent strain was present in 42 % of the samples, followed by other strains found in 18, 10, 9, 8, and 6 %, respectively. Overall, these six variants account for 93 sequences having 100 % identity with clinical strains isolated from patients with acute hepatitis between 2001(Gharbi-Khelifi et al 2006Gharbi-Khelifi et al 2007b;Gharbi-Khelifi et al 2011). We also detected five unique sequences not previously reported in clinical cases, showing 97-99 % identity with Tunisian clinical strains available in GenBank.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The most prevalent strain was present in 42 % of the samples, followed by other strains found in 18, 10, 9, 8, and 6 %, respectively. Overall, these six variants account for 93 sequences having 100 % identity with clinical strains isolated from patients with acute hepatitis between 2001(Gharbi-Khelifi et al 2006Gharbi-Khelifi et al 2007b;Gharbi-Khelifi et al 2011). We also detected five unique sequences not previously reported in clinical cases, showing 97-99 % identity with Tunisian clinical strains available in GenBank.…”
Section: Discussionsupporting
confidence: 52%
“…2. The tree includes a number of representative GenBank IA strains detected in clinical samples in Tunisia from 2001to 2006(Gharbi-Khelifi et al 2006GharbiKhelifi et al 2007b;Gharbi-Khelifi et al 2011), and one IB strain detected in 1981, indicated as accession number followed by strain name. We also included sequences corresponding to strains isolated in the course of a recent clinical study, from the sera of Tunisian patients with acute hepatitis between 2008 and 2013 (Beji et al, manuscript submitted, sequences not yet published in GenBank), indicated as ID number followed by the city and year of collection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guerrero et al, 43 2011, Khelifi et al, 39 2006, Phanuwan et al, 51 2006, O'Brien et al, 29 2017, Khelifi et al, 35 2011, Bai et al, 54 2019, Ahmad et al, 45 2016, Ahmad et al, 46 2015, Ahmad et al, 44 2018, Adefisoye et al, 27 2015, Chigor et al, 20 2012, Ouardani et al, 34 2015.…”
Section: Rt-pcrmentioning
confidence: 99%